ANTIMICROBIAL SUSCEPTIBILITY PATTERN OF UROPATHOGENIC ESCHERICHIA COLI IN A TERTIARY CARE CENTRE AT KANCHEPURAM DISTRICT - ANANDHI LAKSHMANAN; KANAKA P; RADHA MADHAVAN (International Journal of Pharma and Bio Sciences, 2013)
Escherichia Coli is the commonest cause of urinary tract infection (UTI) both in the community and hospital settings. Females experience recurrent UTI in the reproductive age group while men in the older age .Drug resistance among E.coli strains has now become a major concern as clinicians are left with very minimal therapeutic options. To isolate and identify the commonest pathogen causing UTI. To perform the anti-biotic susceptibility pattern of the isolated E.coli. To screen for Extended Spectrum Beta Lactamase (ESBL) and Amp C Beta Lactamase enzyme production. 319 significant urine samples were collected from period of Jan.2011-Jan 2012, in the Department of Microbiology, SRM Medical College Hospital and Research Centre, Kancheepuram district Tamilnadu. The clinical samples were processed and identified as per standard microbiological techniques. Antimicrobial susceptibility was done using Kirby-Bauer disc diffusion method as per CLSI guidelines. ESBL and Amp C production were also identified. Out of 319 samples 200 (62.6%) were identified to be E.coli, the commonest cause of UTI. Females (74%) in the reproductive age group were more affected than males. There was an increase in UTI in male (39.5%) after the age of 45 years. Most of the E.coli strains to be found to be resistant to both Beta Lactam and Non Beta Lactam drugs. Out of 200 E.coli samples 84 (42%) were ESBL producers, 44(22%) were Amp C producers, 38(19%) were Amp C and ESBL co-producers. Multiple drug resistance among uropathogenic E.coli as left clinicians with very few therapeutic options. This study emphasizes on judicious use of antibiotics to prevent both Community and Hospital Acquired Infections.